Impact of thrombus aspiration during ST-Elevation Myocardial Infarction: a six month composite endpoint and risk of stroke analyses of the TASTE trial. Issue 1 (December 2016) - Olivecrona, Göran; Lagerqvist, Bo; Fröbert, Ole; Gudnason, Thórarinn; Maeng, Michael; Råmunddal, Truls; Haupt, Jan; Kellerth, Thomas; Stewart, Jason; Sarno, Giovanna; Jensen, Jens; Östlund, Ollie; et al.
Abstract Background Routine thrombus aspiration during primary percutaneous coronary intervention (PCI) in ST-elevation myocardial infarction (STEMI) did not reduce the primary composite endpoint in the "A Randomised Trial of Routine Aspiration ThrOmbecTomy With PCI Versus PCI ALone in Patients With STEMI Undergoing Primary PCI" (TOTAL) trial. We aimed to analyse a similar endpoint in "The Thrombus Aspiration in ST-Elevation myocardial infarction in Scandinavia" (TASTE) trial up to 180 days. Methods In TASTE, 7244 patients with STEMI were randomised to thrombus aspiration followed by PCI or to PCI alone. We analysed the quadruple composite endpoint of cardiovascular death, cardiogenic shock, rehospitalisation for myocardial infarction, or new hospitalisation for heart failure. Furthermore, an extended net-benefit composite endpoint including stent thrombosis, target vessel revascularization or stroke within 180 days was analysed. Results The primary quadruple composite endpoint occurred in 8.7 % (316 of 3621) in the thrombus aspiration group compared to 9.3 % (338 of 3623) in the PCI alone group (hazard ratio (HR), 0.93; 95 % confidence interval (CI); 0.80 - 1.09, P = 0.36) and the extended net-benefit composite endpoint in 12.0 % (436) vs. 13.2 % (479) (HR, 0.90; 95 % CI; 0.79 - 1.03, P = 0.12). Stroke within 30 days occurred in 0.7 % (27) vs. 0.7 % (24) (HR, 0.89; 95 % CI; 0.51–1.54, P = 0.68). Conclusions A large and an extended composite endpoint analysis from the TASTE trial did not demonstrate any clinical benefit of routine thrombus aspiration during PCI in patients with STEMI. There was no evidence of an increased risk of stroke with thrombus aspiration.